The Adoption of TPACK in Teaching English By EFL Pre-Service Teachers during the Apprenticeship Program in The Merdeka Curriculum Framework - Anggrarini, Natalia; Yulianawati, Ida (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
This study investigates how pre-service teachers use Technological Pedagogical Content Knowledge (TPACK) to teach English during their apprenticeship within the framework of the Merdeka Curriculum. Promoting successful teaching practices in contemporary classrooms requires TPACK, or the integration of technology, pedagogy, and content knowledge. The Merdeka Curriculum provides a framework for applying TPACK principles in practical contexts, with a strong emphasis on adaptability and digital competency. A qualitative descriptive methodology was used to investigate the perspectives and experiences of twenty Pre-Service Teachers from Wiralodra University. The data was collected using a TPACK questionnaire, and the seven TPACK components were measured using a Likert scale. The results indicate that Pre-Service Teachers are highly skilled in integrating technology with content and pedagogy, particularly in planning and aligning digital tools with lesson objectives. However, they encounter challenges in areas such as technical troubleshooting, managing learning complexity, and fostering student-centred exploration using technology. While their ability to design lessons with technological resources is commendable, their readiness to address real-time issues in digital classrooms remains limited. The flexibility of the Merdeka Curriculum enhances their readiness, but deficiencies in technical knowledge and problem-solving skills highlight the need for more targeted instruction and mentoring in these areas. The study underscores the importance of comprehensive preparatory programs to improve TPACK adoption and advocates for ongoing professional development that meets the demands of 21st-century learning. This study successfully advances the implementation of TPACK and emphasizes key areas for enhancement in pre-service teacher education programs aimed at supporting technologically advanced instruction.